Epidemiological studies of burn patients in a burn center in Ghana: any clues for prevention?. Issue 1 (December 2016) - Agbenorku, P.; Aboah, K.; Akpaloo, J.; Amankwa, R.; Farhat, B.; Turkson, E.; Hoyte-Williams, P.; Klutsey, E.; Yorke, J.
Abstract Background Burn injuries are a serious problem worldwide, with most occurrences in low- and middle-income countries. Depending on the extent of injury, burn victims are faced with the challenges of fitting into society due to complications such as extensive scarring and contractures. The current study seeks to determine whether epidemiological studies of burn patients can provide guidelines to enhance burn prevention among the Ghanaian population. Methods Data from the Burns Registry of the Burns Intensive Care Unit (BICU) of Komfo Anokye Teaching Hospital (KATH) was obtained. Data on sex, age, aetiology, % total body surface area (TBSA), and admission outcomes from May 1, 2009, to April 30, 2013, were retrieved for a total of 487 patients during this period. Results Data on burn admissions comprising 263 (54.0 %) males and 224 (46.0 %) females were obtained from the Burns Registry. Children 0–10 years were the most affected age group. The yearly mean % TBSA ranged from 24.74 % to 35.07 %. The majority of burns was caused by scalding. Mortality rates ranged from 8.4 % to 32.0 % during the period under review. Conclusions The study shows that children of 10 years old and below are the most affected group; this may be due to inattention to these children by parents/caretakers. Safety and safe working environments should be provided at home and workplaces, and promotion of education on burn prevention should be intensified.